A Comparative Study of Retiree Expats and Younger Expats: Factors Influencing Expatriates' Selection of Healthcare Facilities in Bali - Putu Sri Maharini; Gede Sri Darma (PT Mattawang Mediatama Solution, 2024)
This research engaged in a comparative investigation of expatriate retirees' and younger expatriates' preferences in selecting healthcare facilities in Bali, applying a comprehensive analytical lens that integrated Maslow's needs theory, consumer behavior theories, and the theory of cultural acculturation.Data were gleaned through in-depth interviews from eight expatriates residing in the popular expat regions of Bali—Sanur, Ubud, and Nusa Dua—divided into retiree and younger age groups. The study found that expatriates' preferences, influenced by various personal, psychological, cultural, and social factors, are vital in their healthcare choices in a foreign land. Their ability to adapt to the local culture and healthcare system, coupled with a positive outlook and successful adjustment, plays a crucial role. It underscores the significance of comprehensive healthcare facilities and proactive government policies to meet the healthcare needs of expatriates locally. This study is distinct for using three theories: Maslow’s Need Theory, Cultural Acculturation, and Consumer Behavior, rarely combined in investigating expatriates' choice of health facilities in Bali.With well-executed strategies addressing expat needs, culture, marketing, staff training, and collaboration, healthcare providers in Southeast Asia can better serve expats, improving their satisfaction and well-being. This study's restricted participant count and qualitative approach can limit the extendibility of findings to a broader populace. The qualitative design's inherent subjectivity may introduce a measure of unintended bias during data interpretation. Moreover, the specific focus on Bali's expatriates might temper the relevance of the study's results to other geographical contexts.